Feasibility and safety of one-stage sacral laminoplasty with autologous sacral laminar reimplantation fixed by absorbable fixation clamps in direct microsurgical treatment of symptomatic sacral extradural spinal meningeal cysts - Yin, Xiaoliang; Zhang, Jia; Ma, Qianquan; Chen, Suhua; Wu, Chao; Yang, Chenlong; Si, Yu; Jiang, Haihui; Guo, Wei; Liu, Ying; Yuan, Huishu; Yang, Jun; et al. (Frontiers in Surgery, 2023)
Introduction: Sacral laminoplasty with titanium mesh and titanium screws can reduce symptomatic Sacral extradural spinal meningeal cysts (SESMCs) recurrence and operation complications. However, due to a defect or thinning of the sacrum, the screws cannot be securely anchored and there are also problems with permanent metal implantation for titanium mesh and screws. We propose that sacral laminoplasty with absorbable clamps can provide rigid fixation even for thinned or defected sacrum without leaving permanent metal implants.In the direct microsurgical treatment of symptomatic SESMCs, we performed one-stage sacral laminoplasty with autologous sacral lamina reimplantation fixed by absorbable fixation clamps. Retrospectively we analyzed intraoperative handling, planarity of the sacral lamina and stability of the fixation based on clinical and radiological data.Results: Between November 2021 to October 2022, we performed sacral laminoplasty with the absorbable craniofix system in 28 consecutive patients of SESMCs. The size of the sacral lamina flaps ranged from 756 to 1052 mm² (average 906.21±84.04mm² ). We applied a minimum of 2(in 4 cases) and up to 4(in 4 cases) craniofix clamps in the operation, with 3 (in 20 cases) being the most common (82.14%，20/28) and convenient to handling. Excellent sacral canal reconstruction could be confirmed intraoperatively by the surgeons and postoperatively by CT scans. No intraoperative complications occurred.Conclusions One-stage sacral laminoplasty with absorbable fixation clamps is technically feasible, and applying 3 of which can achieve a stable fixation effect and are easy for operation. Restoring the normal structure of the sacral canal could reduce complications and improve surgical efficacy.